CLINICAL EFFICACY OF THE FIXED COMBINATION OF AMLODIPINE/VALSARTAN IN PATIENTS WITH ARTERIAL HYPERTENSION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Essential arterial hypertension (AH) is one of the main risk factors for cardiovascular disease. In most patients with hypertension, blood pressure can be well controlled and the risk of cardiovascular disease can be reduced by lifestyle changes in combination with antihypertensive therapy (AHT). The new revision of the European guidelines for the diagnosis and treatment of hypertension confirms the need to start antihypertensive therapy with the appointment of a combination of 2 antihypertensive drugs (AHP), preferably in the form of fixed combinations.